An Investigation of mindfulness training as a self-care strategy for trauma counsellors - Pillay, Kanthamoney (My University, 2020)
This study investigated mindfulness training (MT) as a self-care strategy for trauma counsellors in South Africa, a social context characterised by prominent levels of crime and violence. The aim of the study was to examine the effect of MT on both negative and positive secondary trauma impacts (STI) in relation to aspects of quality of life of trauma counsellors. It was proposed that MT would both reduce negative secondary trauma impacts and increase Compassion Satisfaction and mindfulness capacities and that the beneficial outcomes of MT would be sustained three months post-intervention. A quasi-experimental embedded mixed methods research model was used to investigate the impact of an MT intervention, areas of greatest change in response to the intervention, and the phenomenological experience of subjects during the training. The study population comprised a sample of 58 counsellors from the greater Johannesburg area in South Africa. The quasi-experimental design entailed comparison of pre-test and post-test scores across an MT intervention group and an active Psycho-Educational control group. Quantitative data was analysed using a mixed Between-Within Subjects Analysis of Variance (ANOVA). ANOVA was used to test for mean differences between the two independent groups, while simultaneously subjecting participants to repeated measures, in order to establish whether mean changes in the outcome scores on the dependent variables from pre-test to post-test differed significantly for individuals over time within the two groups. Complementary qualitative data comprising feedback reports from participants were analysed employing Thematic Analysis. Results indicated that MT was effective in reducing negative trauma impacts and in increasing trait mindfulness and that these outcomes were largely sustained over three months post-intervention. MT was found to be associated with variable rates of change on each of the outcomes assessed, with the significant positive impact being on PTSD Checklist for DSM-5 Scale Total scores, followed in descending order by, the Non-Reactivity and Awareness facets of mindfulness, Secondary Traumatic Stress scores, and Burnout scores. There was a relatively smaller impact on Vicarious Traumatisation and a non-statistically significant impact on Compassion Satisfaction. Thematic analysis of the supplementary quantitative data identified four major themes, these being: Paradox or balancing of polarities; Therapeutic skills; Mindsight and Acquisition. The research results indicate that MT is a beneficial intervention for secondary trauma in counsellors engaged in treating traumatised clients
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Doctor of Philosophy (School of Psychology), March 2020